Can three-body recombination purify a quantum gas? - Dogra, L; Glidden, J; Hilker, T; Eigen, C; Cornell, E; Smith, R; Hadzibabic, Z (American Physical Society, 2019)
Three-body recombination in quantum gases is traditionally associated with heating, but it was recently found that it can also cool the gas. We show that in a partially condensed three-dimensional homogeneous Bose gas three-body loss could even purify the sample, that is, reduce the entropy per particle and increase the condensed fraction $η$. We predict that the evolution of $η$ under continuous three-body loss can, depending on small changes in the initial conditions, exhibit two qualitatively different behaviours - if it is initially above a certain critical value, $η$ increases further, whereas clouds with lower initial $η$ evolve towards a thermal gas. These dynamical effects should be observable under realistic experimental conditions.